Four years of the Babangida Administration : achievements and prospects. (Lagos : The Federal Government Printer, 1989)
This book highlights the major achievements that were made in the first four years of the Ibrahim Babangida Administration since coming to power in August 1985. The book comprise of 29 chapters covering sectors like: government and administration; petroleum resources; planning and budget; finance and economic development; agriculture and water resources; rural development; federal capital territory; internal affairs/police; justice; defence; education; employment labour and productivity. Others are: information and culture; social development, youth and sports; information and culture; health; works and housing; science and technology; mines, power and steel; industries; transport; communication; civil aviation; trade; external affairs. The rest include: special duties; political transition programme; performance of the states and local governments; and conclusion.
Includes bibliography
lje 12/12/18
Loans
Keywords: Economy; Nigeria